Implementation of Technology-Based Learning Strategies through Digital Storytelling Applications of Elementary School Students - Putri, Willa; Ardianti, Ike; Wirandani, Wirandani (Study Program of Arabic Language Teaching, 2025)
students' reading interests. The research employed a quantitative experimental design with pre-test and post-test procedures involving the experimental group (using Steller) and the control group (using traditional lecture methods). This study involved 57 students from the 4th-grade classes of Thariq Bin Ziyad and Khalid bin Walid at SDI Ibnu Miskawaih. A sample was selected using the Simple Random Sampling method, with class 4 Khalid as the control group and class 4 Thariq as the experimental group. Data were collected through observation, documentation, questionnaires (pre-test and post-test), and interviews. Data analysis techniques included descriptive and inferential statistics, which involved normality testing, homogeneity testing, and hypothesis testing using an independent sample t-test. The results indicated that the average post-test score of the experimental group (76.21) was higher than that of the control group (72.76), with a significant difference in the t-test (p = 0.000). Using digital storytelling applications improved students' reading interest and learning motivation. This study contributes to the development of technology-based literacy learning at the primary education level, especially in MI.